2009
DOI: 10.1002/cjce.20180
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of gas–solid fluidization in tapered beds

Abstract: Gas-solid fluidization has a wide range of industrial applications like catalytic reactions, combustion, gasification, etc. In a number of these applications, there is particle size reduction during the operation leading to severe entrainment and limitation of operating velocity. The various problems associated with particles of different sizes or changing particles sizes could be overcome by adopting tapered beds in fluidization operation.In the present investigation, the fluidization phenomenon in tapered be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is noted that the conical configuration is essential to fluidize these fine powders having such a wide size distributions to ensure that the larger particles can be fluidized without elutriating the finer particles. A complete description of the hydrodynamics of a conical fluidized bed is outside the scope of this study can be found in the literature [43,44] The bed was heated to 28 o C after which a spraying suspension was pushed with a peristaltic pump through a concentric nozzle at the top of the bed with an inner nozzle (300 m) at a spray rate of 1.00 -1.26 mL/min. Several spraying suspension formulations were considered in this study, which are listed in Table 2.…”
Section: Fluid Bed Coatingmentioning
confidence: 99%
“…It is noted that the conical configuration is essential to fluidize these fine powders having such a wide size distributions to ensure that the larger particles can be fluidized without elutriating the finer particles. A complete description of the hydrodynamics of a conical fluidized bed is outside the scope of this study can be found in the literature [43,44] The bed was heated to 28 o C after which a spraying suspension was pushed with a peristaltic pump through a concentric nozzle at the top of the bed with an inner nozzle (300 m) at a spray rate of 1.00 -1.26 mL/min. Several spraying suspension formulations were considered in this study, which are listed in Table 2.…”
Section: Fluid Bed Coatingmentioning
confidence: 99%